Lumbosacral tuberculosis, a rare manifestation of Pott's disease – How identified human skeletons from the pre-antibiotic era can be used as reference cases to establish a palaeopathological diagnosis of tuberculosis. (January 2023) - Spekker, Olga; Hunt, David R.; Király, Kitty; Kis, Luca; Madai, Ágota; Szalontai, Csaba; Molnár, Erika; Pálfi, György
Abstract: The macromorphological examination of identified human osteological collections from the pre-antibiotic era (e.g., Terry Collection) can provide invaluable information about the skeletal manifestations of tuberculosis (TB) in individuals who did not receive pharmaceutical therapy. With analysis of such collections, new diagnostic criteria for TB can be recognised which can be used in palaeopathological interpretation. The aim of our paper is to provide a reference and aid for the identification of TB in past populations by demonstrating and discussing in detail the vertebral alterations indicative of one of its rare skeletal manifestations, lumbosacral TB. These changes were detected in two individuals from the Terry Collection (Terry No. 760 and Terry No. 1093 ). These two case studies furnish palaeopathologists with a stronger basis for diagnosing lumbosacral TB in skeletons which exhibit similar vertebral lesions from osteoarchaeological series. To illustrate this, an archaeological case from Hungary (KK146 ) is also presented, displaying vertebral alterations resembling that of the two cases from the Terry Collection. Through the demonstrated case studies, we can derive a better insight into the disease experience of people who lived in the past and suffered from TB.